Implementation of digital technology-based stem approach in elementary schools: A systematic literature review - Nasution, Abdul Azis; Simanjuntak, Magda Dwi Hartati; Ghazali, Alfin; Siahaan, Nurhalimah; Lumban Gaol, Manto (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
The advancement of digital technology has driven a transformation in elementary education toward more interactive and collaborative learning aligned with 21st-century competencies. This study conducts a systematic literature review of publications from 2020 to 2025 to map the implementation of digital-based STEM in elementary schools, the learning models employed, the impacts on student outcomes, and the challenges encountered. Article searches were conducted in Google Scholar and the SINTA-indexed database, following the PRISMA 2020 guidelines, yielding 10 studies for thematic analysis. The review indicates the use of interactive e-modules, digital videos, learning applications, virtual laboratories, and educational robotics, which generally enhance learning outcomes, creativity, numeracy literacy, critical thinking, and computational thinking. Key challenges include limited infrastructure, teacher readiness, and inconsistent quality of digital media. The findings underscore the need for policy support, improved teacher competencies, and higher-quality digital learning resources to optimize the integration of digital-based STEM in elementary education.